«Амалий механика» фанини ўқитишда инновацион таълим технологияларидан фойдаланиш истиқболлари (FAN va JAMIYAT, 2021)
The paper presents exact experience in the implementation of a set of innovative teaching methods in the study of applied mechanics in higher educa- tional institutions. The described innovative teaching technologies make it possible to significantly intensify the educational and cognitive activity of